THE CORRELATION BETWEEN NEUTROPHYL-LYMPHOCYTE RATIO AND OPTIC NERVE FUNCTION IN METABOLIC SYNDROME PATIENTS - Prayitnaningsih, Seskoati; Puspasari, Eka Fajarina; Hamid, Aulia Abdul; Rosandi, Rulli (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: The neutrophil lymphocyte ratio (NLR) is a new biomarker in predicting various cardiovascular disorders and was expected to be a biomarker for Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) in metabolic syndrome (MetS) patients. Objective: This study aims to determine the correlation between NLR and optic nerve function in MetS patients. Methods: A cross sectional study involving 42 patients divided into 3 groups, consist of control group(14 patients, 28 eyes), MetS without NAION group(14 patients, 28 eyes) and MetS with NAION group(14 patients, 19 eyes). The study was conducted at Saiful Anwar General Hospital on January-March 2019. Optic nerve function evaluation includes visual acuity (VA) from Snellen chart, Retinal Nerve Fiber Layer(RNFL) from OCT, contrast sensitivity from Pelli Robson test, and visual field defect from Humphrey's perimetry. NLR was calculated and compared among groups using anova test. Then the correlation between NLR and optic nerve function was investigated using Pearson and Spearman test. Results: The NLR was significantly different among groups (p= 0.009), mean of control, MetS without NAION, and MetS with NAION groups 1.70, 1.86, and 2.40 respectively. There were signifficant negative correlation between NLR and visual field defect (p= 0.001,r= -0.487), contrast sensitivity (p= 0.015,r= -0.372), and VA (p= 0.041,r= -0.316), whereas positive correlation between NLR and RNFL statistically insignificant (p= 0.171, r = 0.215). Conclusion: There were signifficant negative correlation between NLR and visual field defect, contrast sensitivity, VA, whereas positive correlation between NLR and RNFL statistically insignificant. NLR is expected to be a potential biomarker for screening NAION in MetS patients.